PENGARUH PERILAKU ORGANISASI TERHADAP KINERJA KARYAWAN DI LOTTE GROSIR BANDUNG - Peddy HF Dasuki; Gema Dwiprakasa Destyan; Anti Nurul Azizah Albasyiroh Nurul Azizah Albasyiroh (IKOPIN, 2019)
This research is tittled Influence of organization behavior on the performance of employees in Lotte Wholesaller Bandung. Organization behavior as general perception that is owned by all member in organization, so the employe which become organization member will have value, confidence, and behavior according to organization. By that definition, then it can be seen that performance of the employe very not important, because decreasing of individual performance or group in a company. The result of this research thats on alpha >6% value of coefficien beta (B) = 0,297 and show T counting of 3,065 significant level 0,004 where smaller than 0,05. Based on the result of analysis and also testing which is conducted and then hypothesis A that states of organization behavior (x) positive effect and significan to employe performance in lotte wholesaller bandung. It can be conclude that Ha accepted.